Microcracking mechanisms of cyclic freeze–thaw treated red sandstone: Insights from acoustic emission and thin-section analysis. (25th April 2022) - Chen, Guoqing; Guo, Tian Yang; Serati, Mehdi; Pei, Bencan
Highlights: F-T treatments cause significant micro-damage as cycle number exceeds a threshold. Cyclic F-T treatments could inhibit the acoustic emission activities of sandstone. The decrease of microcracking behaviour intensity is related to the microdamage. Abstract: We experimentally investigate the effects of cyclic freeze–thaw (F-T) on the microcracking behaviour of sandstone under mode I loading. The centre-cracked Brazilian disc tests were conducted on specimens after various numbers (0, 30, 60, 90, and 120) of cyclic F-T treatments with acoustic emission (AE) monitored. The micro-damage caused by the F-T treatments to the sandstone is examined via thin-section analysis. The results show that the damage degree does not significantly increase until the F-T cycle number exceeds a threshold between 60 and 90. The AE results indicate that the cyclic F-T treatments inhibit the microcracking activities of the sandstone.